Studies on Reactivity of Homo and Heterobimetallic Thiocyanate Bridged Lewis Acid with Schiff Base Derived from 1,2-Diaminopropane with Salicylaldehyde - Shukla, S.N.; Khan, S.; Upadhyay, N.; Tiwari, P.S.; Gour, P.; Srivastava, A. (Asian Journal of Chemistry, 2010)
New complexes of MM(SCN)4 (M = Co2+, Ni2+, M´= Cd2+, Hg2+) with Schiff base derived from 1,2-diaminopropane with salicylaldehyde, have been synthesized and characterized by elemental analyses, molar conductance, magnetic moment, FTIR, electronic and 1H-NMR spectral studies. The softness parameters, ΔTE≠n of complexes have also been calculated to derive the probable structures. The complexes have also been investigated for insecticidal activity against red cotton bug (Dysdercus koenigii).